Energising Fisheries Extension: Bridging Skills Gaps for Furthering Development in Haryana and Punjab - Naila M Bhat; Ananthan P.S.; Neha W. Qureshi; Shivaji D. Argade; Ponnusamy K.; Talib Mohammad (Journal of Indian Fisheries Association, 2023)
A well-prepared workforce is fundamental to the success of any extension organization. Given the rapidtechnological advancements, it's crucial to continually enhance and refresh the skills of human resources. Thisstudy aims to recognize the training requirements of extension personnel within the State FisheriesDepartment (SFD) in the states of Haryana and Punjab. An organized questionnaire was integrated into anonline survey and distributed to both headquarters and district departments. Besides descriptive statistics, theWeighted Sum Method was employed to evaluate training needs, with the scores being standardized. In termsof participation, fisheries district technical SFD staff from Haryana exhibited a 64% response rate, while Punjabrecorded a 60% response rate. Gender distribution showed that about 43% of district technical staff in Punjabwere female, while 11% in Haryana. Across both states, approximately 45% of the district technical staffs’ timewas allocated to extension-related tasks. Notably, the primary training needs identified for SFD staff inHaryana included Better Management Practices (0.86), fish health management (0.83), and recentadvancements in aquaculture technology (0.83). In Punjab, the top training needs for SFD staff encompassedfish nutrition and feed technology (0.85), fish health management (0.83), and recent technologies inaquaculture (0.83). Therefore, it is advisable to develop training programs aligned with these recognizedneeds to strengthen the extension system in both states.